INOVASI PRODUKSI BIOETANOL BERBASIS LIGNOSELULOSA LIMBAH KULIT KOPI (COFFEA SP.) DENGAN KONSEP BIOREFINERY MENGGUNAKAN SACCHAROMYCES CEREVISIAE - Azmi, Haikal; Octaviani, Nazla Fauziyah; Musa'adah, Musa'adah (IPB University, 2025)
Indonesia is the fourth largest coffee exporter in the world, with a market share of around 11%. In 2021, Indonesia's coffee production reached 765,415 tons, generating 382,000 tons of coffee husk waste. However, only about 2% of this amount is utilized, coffee skins contain 20-50% cellulose which hasthepotential to used as a substrate for bioethanol production, a renewable energy source. This study aims to explore innovations in bioethanol production from lignocellulosic coffee pulp waste, particularly through a biorefinery method using Saccharomyces cerevisiae as fermentation agent. The research employs an exploratory descriptive approach, by reviewing relevant scientific articles. The process of converting lignocellulosic substrates into ethanol consists of four main stages in bioethanol production, namely: (1) pretreatment, which can be done physically, chemically, or biologically; (2) hydrolysis of polymers such as cellulose and hemicellulose into simple sugars such as hexose and silose; (3) fermentation of sugars by microorganisms to produce ethanol; and (4) separation and purification of the produced ethanol. The utilization of the biorefinery concept in bioethanol production not only facilitates the conversion of biomass into bioethanol, but also enables the production of other high-value products, such as biohydrogen (environmentally friendly fuel), furfural (resin and composite industry), HMF (bioplastic precursor and furan fuel), xylitol (sweetener in food and pharmaceutical industries), vinasse (organic fertilizer and biomass fuel), organic acids (chemical and pharmaceutical industries), and microbial biomass (high-protein animal feed). Keywords: bioethanol, biorefinery, coffee skin, lignocellulosic waste, saccharomyces cerevisiae